2019
DOI: 10.1016/j.sjbs.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the effect of the pregnancy complicated with the hepatitis B infection on the lying-in women and neonates

Abstract: ObjectiveTo investigate the effect of pregnancy complicated with the hepatitis B infection on the pregnancy outcome, immunological factors and the subgroup of lymphocytes in neonates.MethodsSubjects admitting to this hospital between January 1, 2016 and January 1, 2018 in this study were divided into two groups according to the hepatitis B infection, i.e. the observation group (infection) and the control group (healthy), with 60 subjects in each group. Pregnancy complications and the neonatal complications wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…This information shows that experiencing complications during pregnancy is a risk factor for neonatal death incidence in healthcare facilities in Indonesia. This finding information reinforces the results of previous studies that found similar results [21][22][23] . It is necessary to strengthen the early identification of obstetric complications and urgent intervention to prevent neonatal mortality 24 .…”
Section: Tabel 2 the Results Of Binary Logistic Regression Of Neonatal Death Incidence In The Healthcare Facility Insupporting
confidence: 93%
“…This information shows that experiencing complications during pregnancy is a risk factor for neonatal death incidence in healthcare facilities in Indonesia. This finding information reinforces the results of previous studies that found similar results [21][22][23] . It is necessary to strengthen the early identification of obstetric complications and urgent intervention to prevent neonatal mortality 24 .…”
Section: Tabel 2 the Results Of Binary Logistic Regression Of Neonatal Death Incidence In The Healthcare Facility Insupporting
confidence: 93%
“…In addition to increasing the risk of developing infectious diseases, other studies have investigated whether adhesions caused by tumours, or following caesarean delivery, could increase the probability of HBV infection. For example, Xiao et al found that in a hepatitis B infection group, the incidence of neonatal distress and asphyxia was significantly higher than that in a control group [29]. In another study, Sirilert [30] showed that the incidence of low birth weight was significantly higher among women with a positive HBeAg status relative risk (1.258, 95% CI 1.053-1.505); these results were consistent with those described in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Xiao et al . found that in a hepatitis B infection group, the incidence of neonatal distress and asphyxia was significantly higher than that in a control group [ 29 ]. In another study, Sirilert [ 30 ] showed that the incidence of low birth weight was significantly higher among women with a positive HBeAg status relative risk (1.258, 95% CI 1.053–1.505); these results were consistent with those described in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty eligible articles concerning the effect of HBV infection on pregnancy complications were included to assess the effects of HBV on preterm birth 14–17,19–25,27,28,30–38,40–47 . The results revealed significantly higher rates of preterm birth among HBV+ women compared to HBV− women ( p < 0.01) [OR (95% CI) = 1.26 (1.14–1.40)].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve investigations 15,16,19,20,24,31,32,35–37,44–46 assessed the effects of HBV infection on PROM. However, PROM rate was higher among HBV infected women, it was insignificant ( p = 0.53) [OR (95% CI) = 1.11 (0.79–1.55)].…”
Section: Resultsmentioning
confidence: 99%